Ppargamma2 is a key driver of longevity in the mouse. - Carmen Argmann; Radu Dobrin; Sami Heikkinen; Aurélie Auburtin; Laurent Pouilly; Terrie-Anne Cock; Hana Koutnikova; Jun Zhu; Eric E Schadt; Johan Auwerx (PLoS Genetics)
Aging involves a progressive physiological remodeling that is controlled by both genetic and environmental factors. Many of these factors impact also on white adipose tissue (WAT), which has been shown to be a determinant of lifespan. Interrogating a transcriptional network for predicted causal regulatory interactions in a collection of mouse WAT from F2 crosses with a seed set of 60 known longevity genes, we identified a novel transcriptional subnetwork of 742 genes which represent thus-far-unknown longevity genes. Within this subnetwork, one gene was Pparg (Nr1c3), an adipose-enriched nuclear receptor previously not associated with longevity. In silico, both the PPAR signaling pathway and the transcriptional signature of Ppargamma agonist rosiglitazone overlapped with the longevity subnetwork, while in vivo, lowered expression of Pparg reduced lifespan in both the lipodystrophic Pparg1/2-hypomorphic and the Pparg2-deficient mice. These results establish Ppargamma2 as one of the determinants of longevity and suggest that lifespan may be rather determined by a purposeful genetic program than a random process.